Analysis of handover data between urban and sub-urban area in Selangor: article / Wan Mohd Norsaiful Azuan Wan Daud - Wan Daud, Wan Mohd Norsaiful Azuan (2013)
This paper is on the handover data analysis between urban and sub-urban area in Selangor. The continuation of an active call is one of the important features of a wireless cellular system to provide such a facility by transferring an active call from one cell to another. The objective of this project is to present the study of successful handover and failure between two areas which is at Semenyih, Selangor and Jalan Kuala Selangor, Shah Alam, Selangor. Both these areas are representing the suburban and urban area respectively. The paper focused on data collection of 3G mobile communication by using NEMO drive test provided by Digi Communication Berhad. The collected data consist of strength of signal which is Received Signal Code Power (RSCP) and quality of signal which is Ec/no. Data will be analysis using Microsoft excel and will be export to the Matlab. This data will be presented by using Graphical Using Interface (GUI) create using Matlab software.